DESAIN PRIMER GEN EDNRB EKSON 4 DAN OPTIMASI PCR UNTUK ANALISIS MUTASI GEN PADA HIRSCHSPRUNG DISEASE - Hidayah, Nurul; Ahda, Yuni; Achyar, Afifatul; Atifah, Yusni (Jurnal Biogenerasi, 2025)
EDNRB gene is a gene located on chromosome 13q22, plays a role in the signaling pathway during the development of the ENS intestinal nerves. Mutations in the EDNRB gene in humans are associated with Hirschsprung Disease (HD). Mutations in the EDNRB gene are the second most common cause after the RET gene in cases of HD with a percentage of 5–10%. To detect mutations, PCR products are needed. Primers are one of the basic components of PCR, while optimization of annealing temperature and optimization of primer concentration are factors in the success of primer attachment to the target gene. This study aims to design EDNRB exon 4 gene primers and determine the optimum annealing temperature and primer concentration to amplify the EDNRB gene. Primer design with Geneious Prime, and good primer criteria are analyzed in silico. Optimization of annealing temperature and primer concentration is carried out with gradient PCR and variations in primer concentration. The results of this study obtained the best primers, namely the forward primer 5'- CAGTAAGTGTGGCCTGAAAG-3' and the reverse primer 5'-GTGGAACCGAAGTGACTAGA-3', which amplified the EDNRB gene exon 4. The optimum PCR conditions for amplification of exon 4 of the EDNRB gene were at an annealing temperature of 57.2 ℃ and at a primer concentration of 0.5 μM.